Les langues dans la recherche scientifique et son évaluation: quelques regards - Steffen, Gabriela; Gajo, Laurent; Darbellay, Frédéric (My University, 2019)
Language and discourse practices play a role in scientific research and its evaluation, since they shape knowledge construction. Therefore, it matters in which language research is carried out and knowledge constructed. More precisely, engaging in plurilingual research practices instead of monolingual ones has an impact on the research process and the results obtained. That is because science has its origin in scientific communities and is expressed in discourse activities. Today, however, the diversity of scientific communities and discourse activities tends to be smoothed out to meet the needs of the broad and instant communication of knowledge. This can be witnessed in the emergence of an international scientific macro-community and the uniformization of scientific discourse genres following the same norms and models in a small number of international papers. In this context of the internationalization of scientific research, this paper addresses the tension between the increasing uniformity of scientific practices and language diversity in multilingual Switzerland, from the perspective of research evaluation by the Swiss National Science Foundation. More precisely, this paper shows research councillors' social representations and their views on monolingualism and plurilingualism in science and its evaluation, in relation to their views on science in general and the role of language in research practices.
Keywords: langage; recherche scientifique; évaluation; plurilinguisme; profils de chercheurs; language; scientific research; evaluation; plurilingualism; researcher profiles